2011
DOI: 10.1152/ajpheart.01036.2010
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial inflammation correlates with subject triglycerides and waist size after a high-fat meal

Abstract: A rise in postprandial serum triglycerides (PP-sTG) can potentiate inflammatory responses in vascular endothelial cells (ECs) and thus serves as an independent risk factor for predicting increased cardiovascular morbidity. We examined postprandial triglyceride-rich lipoproteins (PP-TGRLs) in subjects ranging from normal to hypertriglyceridemic for their capacity to alter EC acute inflammatory responses. Cultured human aortic ECs (HAECs) were conditioned with PP-TGRLs isolated from human serum at the peak after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 37 publications
(58 reference statements)
3
57
0
Order By: Relevance
“…Given the functional significance for VCAM-1 as a biomarker for atherogenesis whose expression lies at the convergence of dietary and hemodynamic factors, we used it as a readout of endothelial inflammation in our experiments. We have previously reported that the changes in VCAM-1 expression elicited by TGRL were IRF-1 dependent and strongly correlated with monocyte recruitment to cultured HAECs under shear flow (36,39,44) over a dose range in TNF-␣ that was significantly affected by IRF-1 suppression or overexpression (36). To shed light on the molecular mechanisms by which hydrodynamic shear stress modulates inflammation associated with hypertriglyceridemia, a custom microfluidic device was used that produces a continuous gradient in shear stress over a monolayer of HAECs, allowing visualization of the focal response to inflammation and shear stress during exposure to dietary TGRL (40).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Given the functional significance for VCAM-1 as a biomarker for atherogenesis whose expression lies at the convergence of dietary and hemodynamic factors, we used it as a readout of endothelial inflammation in our experiments. We have previously reported that the changes in VCAM-1 expression elicited by TGRL were IRF-1 dependent and strongly correlated with monocyte recruitment to cultured HAECs under shear flow (36,39,44) over a dose range in TNF-␣ that was significantly affected by IRF-1 suppression or overexpression (36). To shed light on the molecular mechanisms by which hydrodynamic shear stress modulates inflammation associated with hypertriglyceridemia, a custom microfluidic device was used that produces a continuous gradient in shear stress over a monolayer of HAECs, allowing visualization of the focal response to inflammation and shear stress during exposure to dietary TGRL (40).…”
Section: Discussionmentioning
confidence: 99%
“…Human subjects were recruited according to Institutional Review Board-approved protocols at the University of California-Davis. TGRL were collected and characterized as previously described (36,44). Briefly, venous blood was collected after a 12-h overnight fast and again 3.5 h after a standardized moderately high-fat meal (1,230 calories, 42% from fat and 32% from saturated fat).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations